Wild and tame zones in times of disharmony: Muslim boys and belonging in a primary school in Melbourne, Australia. (9th August 2021) - Howie, Luke; Keddie, Amanda; Walsh, Lucas; Wilkinson, Jane
ABSTRACT: This paper features stories about disharmony and social cohesion collected via interviews and focus groups conducted with teachers, school leaders, students, parents and the principal in a multicultural primary school located in a suburb on the outskirts of Melbourne, Australia. This school is located in a low-SES, historically white and working class area that is now home to large communities of immigrants, many of whom are Muslims. These changes have caused considerable anxieties at this school and in the school community. This primary school faces significant challenges in times defined by social disharmony, war and violence, extremism and terrorism, and adversarial public politics. Some Muslims in these communities have been accused of not doing enough to fit in, sticking too steadfast to their values, religion and culture. We argue, following Giroux, that schools must embrace the challenging conversations that can occur when difficult problems are confronted.